Central Infusion of Angiotensin II Type 2 Receptor Agonist Compound 21 Attenuates DOCA/NaCl-Induced Hypertension in Female Rats. (13th December 2015) - Dai, Shu-Yan; Zhang, Yu-Ping; Peng, Wei; Shen, Ying; He, Jing-Jing
Abstract : The present study investigated whether central activation of angiotensin II type 2 receptor (AT2-R) attenuates deoxycorticosterone acetate (DOCA)/NaCl-induced hypertension in intact and ovariectomized (OVX) female rats and whether female sex hormone status has influence on the effects of AT2-R activation. DOCA/NaCl elicited a greater increase in blood pressure in OVX females than that in intact females. Central infusion of compound 21, a specific AT2-R agonist, abolished DOCA/NaCl pressor effect in intact females, whereas same treatment in OVX females produced an inhibitory effect. Real-time RT-PCR analysis revealed that DOCA/NaCl enhanced the mRNA expression of hypertensive components including AT1-R, ACE-1, and TNF- α in the paraventricular nucleus of hypothalamus in both intact and OVX females. However, the mRNA expressions of antihypertensive components such as AT2-R, ACE-2, and IL-10 were increased only in intact females. Central AT2-R agonist reversed the changes in the hypertensive components in all females, while this agonist further upregulated the expression of ACE2 and IL-10 in intact females, but only IL-10 in OVX females. These results indicate that brain AT2-R activation plays an inhibitory role in the development of DOCA/NaCl-induced hypertension in females. This beneficial effect of AT2-R activation involves regulation of renin-angiotensin system and proinflammatory cytokines.